Effect of Agro‐Environmental Factors on the Mineral Content of Olive Oils: Categorization of the Three Major Portuguese Cultivars. (12th April 2016) - Gouvinhas, Irene; Domínguez‐Perles, Raúl; Machado, Nelson; Carvalho, Teresa; Matos, Carlos; Barros, Ana I. R. N. A.
Abstract: The nutritional properties and safety of olive oil are strongly dependent on the content of mineral nutrients and trace elements. Hence, this work assesses the content for quality and toxic metals of olive oils from three major Portuguese cultivars ('Galega', 'Cobrançosa' and 'Picual') obtained from olives in different ripening stages. This evaluation was achieved by flame atomic spectrometry and atomic absorption in a graphite furnace, depending on the metal to be analysed. The results showed mean concentrations of the mineral nutrients Ca and Mg of 20.00 µg g −1, and K and Na of 40.00 and 170.00 µg g −1, respectively, while the trace elements Fe, Co, Cu, Mn, Zn and Ni had mean values of 0.53, ≤ 0.01, 0.33, 0.10, 1.09 and 0.64 µg g −1, respectively. The mean content of the toxic metals Al, Cd, Pb and As were 27.46, 0.03, 0.09 and 0.36 µg g −1, respectively, which were according to the values proposed by European regulations. The evaluation of the data obtained by partial least square regression allowed the identification of the minerals with the strongest potential to discriminate between the season (Na, Cu, Zn and Ni) and the cultivar employed in the olive oil performance (Fe and Mn).